2002
DOI: 10.2501/jar-42-3-7-17
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Affect: Predicting Intention

Abstract: This robust structural modeling study, with over 23,000 responses to 240 advertising messages, found that affect when measured by a visual measure of emotional response dominates over cognition for predicting conative attitude and action. AFFECTIVE AND COGNITIVE-BASED ATTITUDEFor many years, there was a tendency of focusing on cognitive-based attitude, suggesting that, with advertising involvement, cognition predominates over affective processing and that affective reactions are always mediated by cognition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
142
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(166 citation statements)
references
References 31 publications
12
142
3
2
Order By: Relevance
“…A change in affect (negative or positive) as a result of a change in commercial stimuli has recently been shown to be linked to behaviour and behavioural changes, 14 contradicting a previous number of studies that questioned the ability of affect to predict behaviour. 15 In fact, the mid-1970s were filled with disillusionment towards the affective attitude concept.…”
Section: Introductioncontrasting
confidence: 45%
“…A change in affect (negative or positive) as a result of a change in commercial stimuli has recently been shown to be linked to behaviour and behavioural changes, 14 contradicting a previous number of studies that questioned the ability of affect to predict behaviour. 15 In fact, the mid-1970s were filled with disillusionment towards the affective attitude concept.…”
Section: Introductioncontrasting
confidence: 45%
“…These aspects were also mentioned by Karasek and related to workload and stress in his model together with Theorell in 1990(in Gaillard, 2003. In research concerning topics such as picture processing (Bradley et al, 1994) or defining the effects in advertising (Morris et al, 2002) the dimension dominance plays an important role as well. It is recommendable that also in environmental psychology dominance is conceived as an influential factor which deserves serious attention and that this dimension will be rehabilitated.…”
Section: Resultsmentioning
confidence: 99%
“…Developing affective commitment is important for companies because committed customers are less sensitive to price changes and willing to stay in a long-term relationship with the company or brand (Evanschitzky et al 2006). Morris et al (2002) found that customer intention to buy from and continue a relationship with the service provider is strongly influenced by emotions. Similarly, Han and Back (2008) stated that the emotional aspect of affective commitment caused a significant increase in consumer behavioral intentions.…”
Section: Brand Loyaltymentioning
confidence: 99%